COVID-19 vaccine acceptance in South Asia: a multi-country study. (January 2022) - Hawlader, Mohammad Delwer Hossain; Rahman, Mohammad Lutfor; Nazir, Anum; Ara, Tasnim; Haque, Miah Md. Akiful; Saha, Shuvajit; Barsha, Sabrina Yesmin; Hossian, Mosharop; Matin, Kazi Farhana; Siddiquea, Saleka Raihana; Rashid, Md. Utba; Khan, Md. Abdullah Saeed; et al.
Highlights: >60% of survey population in South Asia is willing to be vaccinated against COVID-19 Age, sex, education and comorbidities are associated with vaccine acceptance A large number of people are worried about the effectiveness of COVID-19 vaccine Women were more willing than men to be vaccinated Abstract: Objectives: With COVID-19 vaccination underway, this study aimed to understand belief, attitude and intention of the people in the South Asia region towards the vaccine. Methods: We conducted a cross-sectional study using semi-structured questionnaires among 18201 individuals in four South Asian countries; Bangladesh, India, Pakistan, and Nepal between January 17 and February 2, 2021. We used the Health Belief Model (HBM) to identify the predictors related to vaccine acceptance. STATA (v16.1) was used for all analyses. Results: The percentage of respondents willing to be vaccinated against COVID-19 was 65%, 66%, 72% and 74% for Bangladesh, India, Pakistan and Nepal, respectively. Perceived destructive impact of COVID-19, positive perception of vaccines and concern about possible side effects were significant in modifying respondents' intentions.. In multivariable logistic regression, age, sex, marital status, education, comorbidities, worry about getting infected, perceived COVID-19 impact, belief regarding vaccine efficacy, positive attitude towards mandatory measures, and vaccine availability were found to be associated with vaccine acceptance across countries. Conclusion: Nearabout two-third of the respondants were willing to take COVID-19 vaccine in the four South Asia countries.